H∞–Adaptive H∞ Algorithm-Based State of Charge Estimation Considering the Hysteresis Effect for Lithium Polymer Battery - Feng, Hailong; Wang, Zhifu; Zhang, Fujun (Frontiers in Energy Research, 2021)
Accurate state of charge (SoC) estimation is crucial for the safe and reliable running of lithium-ion batteries in electrified transportation equipment. Based on the first-order RC battery model considering the hysteresis effect, the battery model parameters and SoC simultaneous estimation algorithm combining the H∞ and the adaptive H∞ filterings based on the dual-time frame is firstly proposed in this paper. Then, the battery model with the hysteresis effect is evaluated against the model without that. Subsequently, the proposed algorithm is compared with the dual H∞ algorithm based on the employed battery model. The results demonstrate the excellent performance of the utilized battery model and the integrated algorithm in terms of both the estimation accuracy and the convergence speed.